THE IMPORTANCE OF ENGLISH PROFICIENCY TO FACE ASEAN ECONOMIC COMMUNITY (CASE STUDY: MEDICAL RECORDS AND HEALTH INFORMATION STUDENTS OF POLYTECHNIC PIKSI GANESHA BANDUNG) - Christinawati, Santy (Jurnal Sastra - Studi Ilmiah Sastra, 2019)
The global economic development currently is very rapid. One of the developments that is the ASEAN Economic Community, or it is called AEC. This economic competition is not only about natural resources but also human resource as the most important competition. Each individual is required to be proficient in communication. In this case, the role of English competency is required. The writer measures that English proficiency for Medical Rceords and Health Infromatics students in Polytechnic Piksi Ganesha Bandung as the research object. According to the result of this study, the writer found that the students still need a lot of training to improve their English for communicating. They are not ready yet to compete in ASEAN Economic Community. The main problem found that the students do not improve their vocabularies.